Targeting Antigen‐Presenting Cells to Enhance the Tumor‐Spleen Immunity Cycle through Liposome‐Neoantigen Vaccine - Yu Xu; Bing Wang; Yue Huang; JianPing Liao; Chenyi Wu; Chenxi Zhou; Zishi Kang; Shiyang Jiang; Bing‐Chen Wu; Da Zhang; Ruihua Xu; Xiaolong Liu; et al. (Advanced Science)
Abstract Effective immune responses in both the spleen and the tumor microenvironment are crucial for cancer immunotherapy. However, delivery of neoantigen peptide vaccines to antigen‐presenting cells (APCs) at these sites remains challenging. In this study, LNPsD18, a cationic liposomal formulation that targets and enhances APC uptake at both sites without modifying the targeting ligands is developed. By co‐delivering tumor‐specific neoantigens and a cholesterol‐coupled toll‐like receptor 9 (TLR9) agonist within LNP‐vaxD18, an approximately 60‐fold increase in dendritic cell uptake compared to neoantigen‐adjuvant mixtures is achieved. Intravenous administration of the liposome‐neoantigen peptide vaccine targets both the spleen and the tumor, boosting splenic DC activation, increasing M1‐type tumor‐associated macrophages, and elevating tumor cytokine levels. This reshapes the tumor microenvironment, enhancing IFN‐γ‐producing CD8+ T cells and TCF1+CD8+ T cells within tumors. These outcomes significantly inhibit established tumor growth compared to nontargeted lipid‐based nanovaccine formulations, resulting in improved survival in orthotopic hepatocellular carcinoma and colorectal cancer models. The findings highlight the importance of targeting APCs in both the spleen and tumors to optimize the therapeutic efficacy of liposome‐neoantigen vaccines in cancer treatment.